Daniel and Friends at the Carlisle Indian School - Miller, Robert (Stellenbosch Theological Journal, 2022)
The first chapter of the Book of Daniel presents a narrative of resistance against empire. Reading this text in the context of the Hellenistic world and in conversation with the Carlisle Indian School, a 19th-20th century residential school for the "civilization" of Native Americans, shows both the multiple facets of colonialism and the ways in which resistance is possible and enjoined by the Bible.